2018
DOI: 10.15244/pjoes/76033
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Disperse Dyeing of Ultraviolet-Treated Polyester Fabric Using Disperse Yellow 211

Abstract: Dyes are widely used in the cosmetics, textile, leather, food, paper and plastic industries, but in view of toxicity, these dyes show carcinogenicity towards the environment in the form of effluents [1], due to which the dye bath needs modifications that not only reduce the effluent load but also make the textile processing ecofriendly. Modifications involve the use of modern techniques [2] such as ultraviolet radiation [3], plasma [4], gamma [5-6] ultrasonic, and microwave [7] -all of which make the dyeing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…It is important to note that dyeing with a carrier has significant issues such as an unpleasant odour, toxicity, and environmental contamination. Thus we had to utilise a carrier that was safe for the environment [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that dyeing with a carrier has significant issues such as an unpleasant odour, toxicity, and environmental contamination. Thus we had to utilise a carrier that was safe for the environment [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently utilized ultrasound energy to improve the dyeing of polyester fabrics when dyeing with disperse dyes [3]. One of the environmentally friendly advantages of using microwave energy is rapid heating to high temperatures allowing greater ease of reactions, because the increased frequency of molecular vibrations during microwave irradiation speeds up these reactions [4][5][6][7][8][9][10][11][12][13][14]. Enaminones, pyridone, and pyrazolopyrimidines are key intermediates in the preparation of dispersion dyes due to their low cost and excellent antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that heterogeneous, bright-colored. Azo dyes are widely used for dyeing polyester [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Polyester is one of the polymers containing ester bonds obtained from the polycondensation reaction of diol and dicarboxylic acid ( Figure 1 ) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some recent reports [ 1 , 2 ] have used ultrasound energy to improve the dyeing of polyester fabrics when dyeing with disperse dyes by modifying the surface of the fabric. Additionally, some studies [ 3 ] confirmed that UV rays can be used to improve the color fastness properties without compromising the chemical properties of polyester fabric. One of the environmentally friendly advantages of using microwave energy is the rapid heating to high temperatures that allows for greater ease of reactions, because increasing the frequency of molecular vibrations during microwave irradiation speeds up these reactions as well as reduces the use of solvents [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%